(untitled) (African Journal of Biomedical Research, 2019)
Metabolic alteration is not uncommon in patients with major mental illnesses (MMI) and adipokines are thought to play some roles. Presently, the link between adiposity, adipokines release and MMI is still poorly understood. This study was carried out to determine the possible impact of central adiposity and type of antipsychotic medication on plasma levels of adiponectin and resistin in patients with MMI. Plasma levels of adiponectin and resistin were determined in ninety adults comprising 65 patients with MMI and 25 apparently healthy individuals, who served as controls. Anthropometry and blood pressure (BP) of the study participants were taken using standard methods. Anthropometric indices, BP and plasma level of adiponectin, but not resistin, were significantly higher in patients with MMI compared with the controls. The median plasma adiponectin level was significantly higher in patients with depression compared with patients with schizophrenia and the controls. However, the median plasma levels of adiponectin and resistin were insignificantly higher in patients with central obesity compared with patients without central obesity and in patients on atypical drugs compared with patients on typical drugs. Also, there was no significant difference in the median plasma levels of adiponectin and resistin in patients on clozapine or olanzapine compared with those on risperidone. It could be concluded from this study that patients with MMI have elevated level of adiponectin which does not appear to be influenced by central adiposity and type of antipsychotic medication.